Training and mentorship for youth: Digitalization of tenun motifs to preserve culture in Kampung Wisata Tenun Khatulistiwa Pontianak - Annisa Dina Amalia; Bima Sujendra; Annisa Rizqa Alamri; Fuzy Firda Zhan; M. Marini (Universitas Muhammadiyah Malang, 2024)
The weaving culture is a local tradition owned by many local communities throughout Indonesia, including West Kalimantan. The culture, however, faces several challenges to its preservation due to modernization and cultural changes among younger generations. This community service program aims to preserve the weaving culture in West Kalimantan by delivering training and mentorship to a community of weaving artisans in Weaving Village Pontianak (Kanun), West Kalimantan, on the importance and skill of digitizing motifs and meanings of woven fabrics. This program is delivered by adopting the Community Development Method (CDM) consisting four stages: initiation, action planning, implementation of activities, and evaluation. From the training and mentorship activities, this program results in increasing knowledge and skills among Kanun’s youth regarding the importance of weaving tradition and digital skills to document and preserve the tradition. Therefore, it is recommended that more relevant sustainable programs are developed and integrated in the village development strategies, particularly in documenting and preserving rich histories and meanings related to the weaving tradition in Kanun. In the long term, this skill is hopefully beneficial for the archives of cultural heritage and for attracting new tourists and customers–realizing the “Tourism Village” goal for the targeted community.